Četrt stoletja Konvencije ZN o mednarodni prodaji blaga (CISG) v Sloveniji - Možina, Damjan (Podjetje in delo, 2018)
The paper presents the influence of the UN Convention on International Sale of Goods on Slovenian legislation and legal theory, as well as its application by the courts. Important parts of contract law, in particular some rules on conclusion of contract and damages for breach of contract, in the predecessor of the Slovenian Obligations Code - the Yugoslav Act on Obligations (1978), were modelled after the Hague Uniform Sales Law - the predecessor of CISG. The resemblance of parts of legislation is significant. The CISG has been dealt with relatively well by the legal theory. It is also represented in legal education. In contractual practice, lawyers frequently advise their clients to exclude the application of the convention. However, although numbers of court decisions based on CISG were scarce in the first years, they have increased significantly in recent years. The quality of decisions is rising as well, together with cases of application of foreign legal literature and jurisprudence. In light of the resemblance of parts of contract law, the abundant international literature and jurisprudence on CISG are useful also with regard to the application of domestic law.
Keywords: Konvencija Združenih narodov o mednarodni prodaji blaga; mednarodna prodaja blaga; pogodbeno pravo; pravo mednarodne prodaje blaga; Slovenija; sodna praksa; teorija; zakonodaja